Properties of Biodiesel Derived from Vegetable Oil, Animal Fat and Waste Cooking Oil - Amir, Aziz; Atiqah, Nisfun; R., Mamat; Ahmad Fitri, Yusop; Najafi, G. (2016)
Vegetable oil, animal fat and waste cooking oil can be derived to utilize as biodiesel. The fuel properties of biodiesel are one of the most important parameter to verify the quality of biofuel. The objective of this study is to produce biodiesel from vegetable oils and animal fat and to evaluate their potential as alternative fuel. In this research, methanol solvent (CH3OH) and sodium methoxide catalyst (CH3NaO) were used as a solvent for transesterification process. The key fuel properties such density, viscosity, cetane number, flash point, cloud point and pour point of the biodiesel were measured using the International Standard methods. All of six of crude biodiesel extracted oil namely; palm oil, corn oil, soybean, sunflower, waster cooking oil (WCO) and chicken fat were undergoing these analyses by using different analytical machine. The experimental results show that the properties of six different biodiesel meet the requirement by international standard (EN14214). As a conclusion, the study indicates that vegetable oil, animal fat and WCO derived fuel can be utilized as alternative fuel for biodiesel.